2013
DOI: 10.1007/s11910-013-0352-5
|View full text |Cite
|
Sign up to set email alerts
|

Fourth Cranial Nerve Palsy and Brown Syndrome: Two Interrelated Congenital Cranial Dysinnervation Disorders?

Abstract: Based on neuroimaging data showing absence of the trochlear nerve, congenital superior oblique palsy is now classified as a congenital cranial dysinnervation disorder. A similar absence of the abducens nerve is accompanied by misinnervation to the lateral rectus muscle from a branch of oculomotor nerve in the Duane retraction syndrome. This similarity raises the question of whether some cases of Brown syndrome could arise from a similar synkinesis between the inferior and superior oblique muscles in the settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…Recently, it was proposed that congenital BrS could be regarded as a congenital cranial dysinnervation disorder (CCDD). 16,21,22 Ellis et al 22 reported three cases of congenital Brown syndrome without clinical SO palsy, who exhibited moderate to severe ipsilateral SO hypoplasia. They suggested that these congenital cases might represent CCDD due to absence of normal trochlear innervation and without misinnervation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was proposed that congenital BrS could be regarded as a congenital cranial dysinnervation disorder (CCDD). 16,21,22 Ellis et al 22 reported three cases of congenital Brown syndrome without clinical SO palsy, who exhibited moderate to severe ipsilateral SO hypoplasia. They suggested that these congenital cases might represent CCDD due to absence of normal trochlear innervation and without misinnervation.…”
Section: Discussionmentioning
confidence: 99%
“…8 Co-contraction of the superior oblique, medial rectus, or inferior oblique muscles can explain the findings seen in some patients with Brown syndrome. 4,6,8 The electromyographic exam performed in our patient did not detect existence of paradoxical innervation. This and the complete spontaneous resolution that occurred in our patient after a 3-year follow-up lead us to the final diagnosis of congenital Brown syndrome related to primary structural abnormalities of the complex superior oblique muscle-tendon-trochlea.…”
Section: Discussionmentioning
confidence: 98%
“…8 Congenital fourth nerve palsy probably comprises a number of different etiologies that primarily include neurogenic cases with congenital absence of the trochlear nerve or anomalous innervation that leads to secondary hypoplasia or atrophy of the superior oblique muscle with laxity or aplasia of its tendon. 5,6,8 In clinical practice, this situation is particularly common due to the small size of the fourth cranial nerve and long anatomical course. 8 Congenital Brown syndrome has long been attributed to structural abnormalities of the superior oblique muscle, tendon, or trochlea, which can explain the restricted elevation in adduction on forced duction test.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations